Implementasi Konsep Golden Treasure terhadap Galeri Jember Fashion Carnaval di Jember - Budiono, Christine Natalia (Intra, 2013)
A talented designer from Jember city who founded a fashion house Dynan Fariz International High Fashion Center. Dynan Fariz has a dream to make Jember city as a fashion city, so he founded the Jember Fashion Carnaval. Jember city is known identical withÂ  JFC. The interior design gallery of Jember Fashion Carnaval in Jemberâs city, will make the city the center of fashion, So people can see the works of JFC without waiting once a year, and can provide positive impacts for the community and the district administration of Jember. By creating a gallery that has an entertainment value, educational, recreational, able to give special image for visitors, and can provide positive impacts for Jemberâs city as a fashion city. To support the interior design requires data and formulation of the problem as a benchmark. The scope of the design in this gallery include best costume gallery, gallery of unique costume, costume next gallery, photo studio JFC, souvenir shop, a demo area, area history, profiles and awards area. This gallery is expected to be a means for young people to channel their talents and Â in future JFC can has positive impacts. Because of that the concept of Golden Treasure gallery can illustrate that the JFC is one of the valuable asset of Jemberâs city.